Geochemistry of altered phases, basalts and sediments of ODP Site 136-843 - D Guy Waggoner (PANGAEA, 1993)
40Ar-39Ar incremental heating experiments on a relatively unaltered basalt from Site 843 yield a crystallization age of 110 ± 2 Ma for the central Pacific Ocean igneous basement near Hawaii. Previous estimates of the age of the basement inferred by indirect methods and from radiometric dates of the South Hawaiian Seamounts are too young by 20-30 m.y. Phyllosilicate alteration minerals from veins in the Site 843 basalts define a Rb/Sr isochron with an age of 94.5 ± 0.5 Ma. The isochron records the last equilibration of the phyllosilicate minerals with a hydrothermal fluid at about 16 m.y. after the formation of the igneous basement. The last event recorded by calcite veins is the sealing of the crust by a sufficient thickness of sediment to impede the free circulation of seawater into the crust. The chemistry of the alteration minerals indicates the rare earth elements in the hydrothermal solutions were derived from alteration of the basalts and, furthermore, were transported in solution as metal species and carbonate complexes. Calcite with approximately seawater 87Sr/86Sr, but Sr contents too low to precipitate directly from seawater, is suggested to have formed at a late stage in the alteration history of the crust by the reaction of seawater with calcite precipitated earlier from basalt-dominated hydrothermal fluids.
Supplement to: Waggoner, DG (1993): The age and alteration of central Pacific Oceanic crust near Hawaii, Site 843. In: Wilkens, RH; Firth, J; Bender, J; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 136, 119-132, https://doi.org/10.2973/odp.proc.sr.136.212.1993